2009
DOI: 10.1016/j.it.2009.04.007
|View full text |Cite
|
Sign up to set email alerts
|

T-cell immunosenescence: lessons learned from mouse models of aging

Abstract: It is well established that increasing age is associated with a decreased capacity of the immune system to mediate effective immune responses to vaccination and invading pathogens. Because of the inherent limitations of conducting experiments in humans, much of what we have learned is owed to the utility of experimental mouse models of aging. Recent studies performed in the mouse have demonstrated mechanisms responsible for age-related declines in the function of CD4+ and CD8+ cells. This review describes key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
133
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(141 citation statements)
references
References 48 publications
6
133
1
1
Order By: Relevance
“…2 As humans age, immune responses become impaired, characterized by (1) reduced lymphopoiesis of new na€ ıve B and T cells, with novel BCRs 6 and TCRs, 7 respectively, (2) reduced dendritic cell (DC) function resulting in poor responses to inflammatory signals and lowered capacity to present antigen and to activate adaptive immune responses, 8 (3) poor germinal center formation, site of B cell expansion and selection, 9 and (4) decreased potential for T cell expansion, expression of activation markers, production of cytokines, diversity of TCR repertoire and delayed T cell responses to antigen. 7,10 Thus, these changes during aging help to explain the increased susceptibility to infection and reduced response to vaccinations in the elderly population. 3,11,12 Previous work has characterized the presence of immune cells organized as ectopic lymphoid structures, referred as tertiary lymphoid structures (TLS), in the tumor of non-small cell lung cancer (NSCLC) patients.…”
Section: Introductionmentioning
confidence: 99%
“…2 As humans age, immune responses become impaired, characterized by (1) reduced lymphopoiesis of new na€ ıve B and T cells, with novel BCRs 6 and TCRs, 7 respectively, (2) reduced dendritic cell (DC) function resulting in poor responses to inflammatory signals and lowered capacity to present antigen and to activate adaptive immune responses, 8 (3) poor germinal center formation, site of B cell expansion and selection, 9 and (4) decreased potential for T cell expansion, expression of activation markers, production of cytokines, diversity of TCR repertoire and delayed T cell responses to antigen. 7,10 Thus, these changes during aging help to explain the increased susceptibility to infection and reduced response to vaccinations in the elderly population. 3,11,12 Previous work has characterized the presence of immune cells organized as ectopic lymphoid structures, referred as tertiary lymphoid structures (TLS), in the tumor of non-small cell lung cancer (NSCLC) patients.…”
Section: Introductionmentioning
confidence: 99%
“…Thymic involution cannot solely account for impaired immune responses as additional T‐cell intrinsic defects appear in ageing naïve T cells due to prolonged post‐thymic lifespan (Haynes & Swain, 2006; Maue et al ., 2009; Tsukamoto et al ., 2009). More specifically, TCR activation is blunted with ageing due to increased cytoplasmic concentration of phosphatases known for inhibiting TCR signaling (Li et al ., 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Repeated observations revealed that beside scarcity of T‐cell precursors in the pre‐immune repertoire, IL‐2 production, cell surface expression of CD25, and T‐cell proliferation are all greatly reduced in ageing hosts (Haynes & Swain, 2006; Maue et al ., 2009; Tsukamoto et al ., 2009). Elevated secretion levels of pro‐inflammatory cytokines such as interferon (IFN)γ caused by the accumulation of CD44 hi T cells were also reported to play a role in accelerating age‐related immunosenescence (Zhang et al ., 2002; Decman et al ., 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations